Sukuk and Inflation Dynamics in Indonesia: A Time Series Linear Model Investigation - Pimada, Laila M.; Miranti, Titis (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study examines the impact of sukuk on inflation in Indonesia, considering the interplay of macroeconomic factors during the post-COVID-19 recovery period. Employing a time series linear model (TSLM) with monthly data from January 2019 to March 2024, we investigate the relationship between sukuk outstanding and inflation (Consumer Price Index), controlling for industrial production, exchange rate, interest rate, and Composite Leading Indicator (CLI). Results reveal a significant positive relationship between sukuk and inflation, suggesting that increased sukuk outstanding is associated with higher inflation rates. This finding contributes to the existing literature by providing empirical evidence of the inflationary impact of sukuk in Indonesia, especially in the context of post-pandemic recovery. The study also identifies significant positive relationships between inflation and interest rate, as well as inflation and CLI, highlighting their roles in driving inflation. While the exchange rate also exhibits a positive relationship with inflation, industrial production shows a negative association, suggesting a potential dampening effect on inflation. The model demonstrates strong explanatory power, with an adjusted R-squared of 0.9818, indicating that the included variables effectively capture the variation in inflation. These findings offer valuable insights for policymakers in formulating effective inflation management strategies and ensuring macroeconomic stability in Indonesia's post-pandemic recovery.